Assessing Antibiotics Biodegradation and Effects at Sub-inhibitory Concentrations by Quantitative Microbial Community Deconvolution - Özel Duygan, Birge D.; Gaille, Caroline; Fenner, Kathrin; van der Meer, Jan R. (Frontiers in Environmental Science, 2021)
Antibiotics in the environment cause widespread concern as a result of their potent inhibitory action on microbial growth and their role in potentially creating selective conditions for proliferation of antibiotic resistant bacteria. Comprising a carbon skeleton, antibiotics should be amenable to microbial biodegradation, but this is still largely uncharted territory because of their simultaneous strong toxicity. In this study, we estimated potential antibiotics degradation by and effects on mixed microbial communities at concentrations sufficiently high to allow sensitive detection of biomass growth, but simultaneously, low enough to mitigate their toxic action. We used three different mixed inoculum sources freshly derived from freshwater, activated sludge or soil, and tested a series of 15 antibiotics from different classes at 1 mg C-carbon l–1 dosage. Consistent community growth was observed for freshwater and activated sludge with ampicillin, erythromycin and chloramphenicol, and with sulfomethoxazole for activated sludge, which was accompanied by parent compound disappearance. Community growth could be attributed to a few subclasses of recognized cell types by using supervised machine-learning-based classifiers. Most other tested antibiotics resulted in inhibition of community growth on background assimilable organic carbon, concomitant with altered composition of the resulting communities. We conclude that growth-linked biodegradation of antibiotics at low concentrations may be present among typical environmental microbiota, but for a selected subset only, whereas for the majority of antibiotics negative effects prevail without any sign of productive growth.